Identification of Active Species in Photodegradation of Aqueous Imidacloprid over g-C3N4/TiO2 Nanocomposites - Thawanrat Kobkeatthawin (2022)
In this work, g-C3N4/TiO2 composites were fabricated through a hydrothermal method for the efficient photocatalytic degradation of imidacloprid (IMI) pesticide. The composites were fabricated at varying loading of sonochemically exfoliated g-C3N4 (denoted as CNS). Complementary characterization results indicate that the heterojunction between the CNS and TiO2 formed. Among the composites, the 0.5CNS/TiO2 material gave the highest photocatalytic activity (93% IMI removal efficiency) under UV-Vis light irradiation, which was 2.2 times over the pristine g-C3N4. The high photocatalytic activity of the g-C3N4/TiO2 composites could be ascribed to the band gap energy reduction and suppression of photo-induced charge carrier recombination on both TiO2 and CNS surfaces. In addition, it was found that the active species involved in the photodegradation process are OH• and holes, and a possible mechanism was proposed. The g-C3N4/TiO2 photocatalysts exhibited stable photocatalytic performance after regeneration, which shows that g-C3N4/TiO2 is a promising material for the photodegradation of imidacloprid pesticide in wastewater.